0.18(12)+0.03=(18+x)

Simple and best practice solution for 0.18(12)+0.03=(18+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.18(12)+0.03=(18+x) equation:


Simplifying
0.18(12) + 0.03 = (18 + x)

Multiply 0.18 * 12
2.16 + 0.03 = (18 + x)

Combine like terms: 2.16 + 0.03 = 2.19
2.19 = (18 + x)

Remove parenthesis around (18 + x)
2.19 = 18 + x

Solving
2.19 = 18 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
2.19 + -1x = 18 + x + -1x

Combine like terms: x + -1x = 0
2.19 + -1x = 18 + 0
2.19 + -1x = 18

Add '-2.19' to each side of the equation.
2.19 + -2.19 + -1x = 18 + -2.19

Combine like terms: 2.19 + -2.19 = 0.00
0.00 + -1x = 18 + -2.19
-1x = 18 + -2.19

Combine like terms: 18 + -2.19 = 15.81
-1x = 15.81

Divide each side by '-1'.
x = -15.81

Simplifying
x = -15.81

See similar equations:

| P=2a+b(findb) | | 3x+2-5x=8x+22 | | x-9=-31 | | 1/2(5x+4)-1/3(x+7)=4 | | 3*1/3*1*5/12= | | q-37=x | | 3(-2+X)=4X-1/3 | | 37-q=x | | p/7=-12 | | 12/(x-9)=6/9 | | u/4=14 | | 4X+9=3(X) | | 12(3x+4)-6(2x-3)=4x-74 | | 6x=-x+147 | | z+17/23=-4/23 | | 7.26-0.3x=12 | | -2y-x-6=0 | | 5+2p-3=9p+4-6p | | g/9=-11 | | g/9=-1 | | 10e^6x=16 | | 5X-4=15+X | | 6(2x-1)-(11x+6)=7 | | 5/4x=20 | | x+54=70 | | -126= | | -6.1(4s+6)-1.8(2s-4)= | | 12-10=x/5 | | 18^7*6^2*3^-7/6^10 | | 9x-3x= | | r/6=-12 | | 3-18=3z |

Equations solver categories